Linking Quality Improvement and Health Information Technology through the QI-HIT Figure 8 - Jamieson, Trevor; Mamdani, Muhammad M.; Etchells, Edward (Applied Clinical Informatics, 2019)
The implementation of health information technology (HIT) is complex. A method for mitigating complexity is incrementalism. Incrementalism forms the foundation of both incremental software development models, like agile, and the Plan-Do-Study-Act cycles (PDSAs) of quality improvement (QI), yet we often fail to be incremental at the union of the disciplines. We propose a new model for HIT implementation that explicitly links incremental software development cycles with PDSAs, the QI-HIT Figure 8 (QIHIT-F8). We then detail a subsequent local HIT implementation where we demonstrated its use. The QIHIT-F8 requires a reprioritization of project management activities around tests of change, strong QI principles to detect these changes, and the presence of both baseline and prospective data about the chosen indicators. These conditions are most likely to be present when applied to indicators of high strategic importance to an organization.
Keywords: implementation and deployment; testing and evaluation; system improvement; outcome and process assessment; inpatient care